An investigation of predictors of mental health in single men and women experiencing homelessness in three Canadian cities. Issue 1 (2nd January 2018) - Cherner, Rebecca A.; Farrell, Susan; Hwang, Stephen W.; Aubry, Tim; Klodawsky, Fran; Hubley, Anita M.; Gadermann, Anne; To, Matthew J.
ABSTRACT: Homelessness is related to poorer mental health, yet, there is limited understanding of the predictors of mental health of men and women experiencing homelessness. To support service providers in identifying individuals who might be at particular risk of poor mental health, this study investigated the predictors of mental health in 501 single men and women experiencing homelessness in Vancouver, Toronto, and Ottawa, Canada. Data were obtained via in-person, structured interviews. In order to identify whether predictors differ by gender, multiple linear regressions were conducted separately for men and women. Mental health status was measured by the Mental Component Summary score of the 12-item Short-Form Health Survey. Better mental health for men and women was associated with the presence of fewer chronic health conditions and a higher level of social support. An older age, not having experienced a recent physical attack, and absence of a mental health diagnosis were related to better mental health for women. The absence of unmet mental health needs within the past 12 months was associated with better mental health for men. The study highlights differences in factors associated with mental health for men and women. Service providers should be aware of the association of these factors with mental health to guide assessment and service planning.